2013
DOI: 10.4103/0970-2113.120604
|View full text |Cite
|
Sign up to set email alerts
|

Is serum cholesterol a risk factor for asthma?

Abstract: Background:Proinflammatory role of serum cholesterol in asthma has been recently explored with contradicting results. Clarity on the link between serum cholesterol and asthma may lead to new evolutions in planning management strategies. The objective of our study was to examine the relationship between the serum cholesterol, asthma and its characteristics.Materials and Methods:A total of 40 asthmatics and 40 normal subjects were examined cross-sectionally and their serum fasting cholesterol and serum high sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…This is consistent with other studies, and overcrowding is known to be a risk factor for asthma [19][20][21]. Overcrowding is common in Indian population and may be viewed as a marker for poor indoor hygiene and consequently increased exposure to various indoor allergens (such as house dust mites, animal dander, cockroaches, fungi, and molds) that are known to play an important role in the pathogenesis of asthma [19,20]. The odds of rhinoconjunctivitis were lower in participants with pucca/semipucca house type.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with other studies, and overcrowding is known to be a risk factor for asthma [19][20][21]. Overcrowding is common in Indian population and may be viewed as a marker for poor indoor hygiene and consequently increased exposure to various indoor allergens (such as house dust mites, animal dander, cockroaches, fungi, and molds) that are known to play an important role in the pathogenesis of asthma [19,20]. The odds of rhinoconjunctivitis were lower in participants with pucca/semipucca house type.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of several studies are consistent with our results. Hypercholesterolemia was found to increase the probability of asthma in both adolescents and adults [ 6 , 17 ]. Additionally, a Taiwan study reported a positive relationship between TC level and asthma development only in boys [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, hypercholesterolemia plays a pro-inflammatory role, inducing the release of inflammatory cytokines and upregulating cellular adhesion molecules in the endothelium [ 18 , 19 ]. Furthermore, dyslipidemia may also potentiate eosinophilic inflammation that is implicated in other conditions of asthma pathophysiology, such as mucus hypersecretion, bronchial hyperresponsiveness, and subepithelial fibrosis [ 6 , 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…2) and asthma. 2630 An increased red blood cell count is not a recognized biomarker of asthma, but could conceivably reflect a number of factors including hypoxemia (11.1% with an acute asthma diagnosis also had a chronic obstructive pulmonary disease diagnosis), or hemoconcentration resulting from acute dehydration during an asthma attack, but the nature of this retrospective study does not allow us to consult the full medical records to investigate this.…”
Section: Resultsmentioning
confidence: 99%